Investigation on the lubrication potential of graphene oxide aqueous dispersion for self-mated stainless steel tribo-pair - Singh S.; Chen X.; Zhang C.; Tyagi R.; Luo J. (My University, 2025)
Due to high concerns for environmental protection and resource conservation, water-based lubrication with some additives is gaining the attention of researchers. Hence, the present study has been conducted to explore the tribological potential of lubricant containing graphene oxide (GO)as an additive in water. The friction and wear performance was evaluated for self-mated SS 304 under reciprocating sliding using a ball-on-disc configuration under high contact stress (∼1.42 GPa or higher). The results indicate that 0.1 wt% is the optimum content of graphene oxide under the conditions used in the study and has the capability to reduce friction coefficient from 0.56 (pure water)to 0.12 with an attendant reduction in wear volume by 68%. The enhancement in tribological performance has been attributed to the formation of a low shear strength tribo-layer of graphene on the surface of both the ball and the disc. The effect of normal load and sliding speed for optimized concentration was also investigated. The average coefficient of friction was observed to increase with load whereas, it was observed to decrease with increase in speed till 0.05 m/s beyond which it increased. © 2019